Effect of citrate buffer on hydrogen production by photosynthetic bacteria. (March 2022) - Guo, Siyi; Lu, Chaoyang; Wang, Kaixin; Wang, Jian; Zhang, Zhiping; Liu, Hong; Jing, Yanyan; Zhang, Quanguo
Graphical abstract: Highlights: Citrate buffer to enhance pH stability of fermentation broth. Citrate buffer of 0.05 mol/L increased hydrogen production by 42%. Citrate buffer at pH 6 increased hydrogen production by 48.36%. Abstract: The effect of citrate buffer on biohydrogen production using photosynthetic bacteria was studied. The study was performed in two steps. First, specific concentrations of citrate and sodium citrate as buffers were mixed into batch cultures, and the effects of these buffers on fermentation broth characteristics and biohydrogen production were analyzed. The maximum overall biohydrogen yield of 411.4 mL, which was 42% higher to the control group, was obtained with 0.05 mol/L citrate buffer. Then, the effect of 0.05 mol/L citrate buffer on biohydrogen yield at different pH values (5.5–7.5) were explored. The maximum biohydrogen yield of 429.82 mL was obtained at pH 6, and the final pH values were effectively controlled. The findings indicated that citrate buffer seriously affected the pH of the reaction liquid. The results provide technical support to stabilize the pH of photo-fermentation broth and improve biohydrogen production performance.